2021
DOI: 10.1111/ele.13847
|View full text |Cite
|
Sign up to set email alerts
|

Stress causes interspecific facilitation within a compost community

Abstract: Ecological theory predicts interactions between species to become more positive under abiotic stress, while competition should prevail in more benign environments. However, experimental tests of this stress gradient hypothesis in natural microbial communities are lacking. We test this hypothesis by measuring interactions between 10 different members of a bacterial community inhabiting potting compost in the presence or absence of toxic copper stress. We found that copper stress caused significant net changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 56 publications
6
19
1
Order By: Relevance
“…Since the degradation of MPs is difficult, microbes may tend to cooperate to make use of them. This fits quite well to the stress gradient hypothesis that positive interactions tend to dominate over competitive interactions in "harsher" environments, as found in plants and the compost community of copper stress [68,69]. We further found that the relationship between plastisphere bacterial zOTUs was predominantly positive in the soil ecosystem.…”
Section: Discussionsupporting
confidence: 88%
“…Since the degradation of MPs is difficult, microbes may tend to cooperate to make use of them. This fits quite well to the stress gradient hypothesis that positive interactions tend to dominate over competitive interactions in "harsher" environments, as found in plants and the compost community of copper stress [68,69]. We further found that the relationship between plastisphere bacterial zOTUs was predominantly positive in the soil ecosystem.…”
Section: Discussionsupporting
confidence: 88%
“…The present result that higher stress favors negative interactions was, however, inconsistent with some previous studies looking at much-less-complex communities ( 14 , 16 , 59 ). Hesse et al also showed that toxic copper promoted positive interactions in a 10-species compost microbial community ( 14 ), Piccardi et al showed that toxicity drives facilitation between 4 bacterial species ( 16 ), and Yu et al showed that nitrite, which acts as a stressor for the microbial community, enabled a 13-species microbial community of municipal wastewater to have fewer negative interactions ( 59 ). These studies are all consistent with the predictions of SGH, unlike the present study looking at the temperature stresses.…”
Section: Discussioncontrasting
confidence: 99%
“…Soil microbiota play essential roles in diverse ecosystem processes ( 1 5 ), such as nutrient cycle ( 6 ), carbon cycle ( 7 , 8 ), pollutant degradation ( 9 , 10 ), plant growth promotion ( 11 , 12 ), and climate regulation ( 13 ). Moreover, the structure of the interaction network has been related to the function and dynamics of the microbial community ( 14 18 ), which agrees with community ecological theories ( 19 ). Besides, with the help of network science tools, the community's network structure has also been used to identify functionally essential species in microbial ecology ( 20 23 ).…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Figure 5C indicates an emergence of faciliatory interactions only under antibiotic exposure. This pattern is consistent with the stress-gradient hypothesis, which predicts that positive species interactions are enhanced under environmental stress [90][91][92] .…”
Section: Discussionsupporting
confidence: 89%